Kay Boyle and Richard Wright, 1948-1960: A “Friendship Forever” in “a difficult time” - Toru KIUCHI (E-REA)
This article offers a brief examination of the friendship of Kay Boyle and Richard Wright, from 1948, when they first met in Paris, till Wright’s death in 1960. The lives and activist careers of the two writers—who both fought against racial prejudices and for more social justice in the United States—often intersected, as in 1937, for instance, when they became involved with Nancy Cunard in the defense of the “Scottsboro Boys.” In the 1950s, when they were both suspected to be Communist sympathizers, Boyle and Wright—who kept in touch thanks to the editor Edward Aswell— never failed in supporting each other.